A Comparative Study of Fundamental Population Growth Models Applied to Kaski District of Nepal - Bhadra Raj Tripathi; Iswar Mani Adhikari (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Exponential, Logistic, and Gompertz are three classical population growth models. These are also known as fundamental population growth models for measuring the population growth rate and estimating the population. Using census datasets from five decades for the Kaski district, we aim to produce a comparative study of these models and their mathematical formulations, including some of the interesting properties. Here, we present the differential equations and their respective solutions related to these models. Various computational tools are also used for their evaluations. These are compared with respect to their calibration, projections, and mathematical perspectives. Their estimation errors and the best fit are also analyzed with respect to the population of Kaski District. Finally, we recommend the better model for population forecasting.